Influence of carbonation on chloride binding of mortars made with simulated marine sand. (11th October 2021) - Sun, Ming; Sun, Congtao; Zhang, Peng; Liu, Nazhen; Li, Yantao; Duan, Jizhou; Hou, Baorong
Highlights: The incorporation of SCMs can significantly increase the carbonation zone depth in mortars. Two peak values for chloride content were observed in mortars with simulated marine sand under accelerated carbonation. Under accelerated carbonation, the chloride binding capacity was initially extremely low, then gradually increased, and finally stabilized with increased depth in the mortars containing simulated marine sand. The incorporation of SCMs decreased the chloride binding capacity of the mortars under carbonation. Abstract: This study investigated the effects of carbonation on the chloride binding of mortars containing simulated marine sand. Various admixtures were added, and metakaolin (MK), fly ash (FA), nano-Al2 O3 (NA), and aluminum (A) were considered as supplementary cementitious materials (SCMs) for use in mortars. Changes in free chloride content, total chloride content, bound chloride content, chloride binding rates, and pH values as a function of mortar depth were analyzed, and the effects of carbonation on the hydration products were also assessed. The results indicated that in the place of cement, SCMs could significantly increase the carbonation zone depth in mortar. The chloride ions migrated outward and inward under accelerated carbonation conditions in the mortar, generating two peak values for the chloride content in the mortars. Consequently, the incorporation of SCMs was beneficial for chloride ion migration in mortars under carbonation. Additionally, the bound chloride content and chloride binding rates were initially extremely low, then gradually increased, and finally stabilized with increased depth in the mortars under carbonation. Furthermore, the incorporation of SCMs resulted in the decreased chloride binding capacity of the mortars under accelerated carbonation, and Friedel's salt gradually decomposed with carbonation.